(3eSJbUi GdGLJgGO aj TQM PNjQI GdeYGO hGdGQTGOs - (3GdMSjfj, GdJHQjRj, GdbRhjfj, MSjf Hf EHQGgje Hf eMeO nerYoUhe, J (B1208(3g`s
(3ChdgG (B:s
(3GdMeO ddg Pj GdLhO hGdEfYGe(B...(3CeG HYO(B...(3Efg deG cGf GdYdhe eY JTYH afhfgG hJaQb CZUGf CUhdgG SHHG dGeJjGR fhY GdEfSGf(B...s
(3BNQgG (B:s
...(3hHjGf GdMLL hGdOdjd hPcQ GdNdGa hGdhaGb Ydi GdJaUjd jWdH ef GdeHGMK(B...(3HYhf GdQH GdLdjd(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B230s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B600s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis